EMPOWERING THE WARA VILLAGE COMMUNITY IN DETERMINING MARKETING STRATEGIES FOR LOCAL RICE MSME PRODUCTS THROUGH BRAND INTRODUCTION & FORMATION - Nurindah Sulistiowati, Wahyuni; Tuhuteru, Sumiyati; Srimanti, Yulianti; Dabi, Lukas (LPPM Univ. Ibn Khaldun Bogor, 2025)
MSMEs in Wara Village, Wamena, produce a superior product, high-quality local rice, which has not been fully maximized in terms of marketing. The main obstacles faced by the local community are a lack of understanding of modern marketing strategies and the suboptimal use of digital technology. Marketing activities still rely on conventional methods without proper packaging, branding, or promotion through digital media. Furthermore, limited internet access and low levels of digital literacy exacerbate the situation. As a result, local rice products struggle to compete and lack adequate bargaining power in the market. Therefore, capacity building in the marketing sector is necessary to support the optimal development of product potential. The solution is to organize a socialization of product marketing strategies tailored to the real needs of local businesses. Using concrete case studies and a participatory approach, this socialization increases knowledge of marketing mix concepts and brand creation. This activity significantly contributes to strengthening the marketing capacity of MSMEs and building the identity of local rice products. Going forward, through ongoing mentoring, it is hoped that the Wara Village community will be able to independently expand the market and increase the economic value of their products.